2020
DOI: 10.3390/cells9030743
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Interaction of γδ T-Cells and B-Cells

Abstract: Right after the discovery of γδ T-cells in 1984, people started asking how γδ T-cells interact with other immune cells such as B-cells. Early reports showed that γδ T-cells are able to help B-cells to produce antibodies and to sustain the production of germinal centers. Interestingly, the presence of γδ T-cells seems to promote the generation of antibodies against "self" and less against challenging pathogens. More recently, these hypotheses were supported using γδ T-cell-deficient mouse strains, in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 91 publications
(118 reference statements)
0
39
0
3
Order By: Relevance
“…Given that GBS affects more males than females, this could imply that the immune changes seen with aging in males may be a contributing factor to the pathogenesis of GBS via alterations in B cells. In addition, there have been some studies suggesting that γδ T cells and B cells interact (Häcker et al, 1995 ; Rampoldi et al, 2020 ). More specifically, Häcker et al have found that when autologous B cells were used to stimulate γδ T cells in culture, it led to an increase in the percentage of Vδ1 + cells (Häcker et al, 1995 ).…”
Section: Acute Inflammatory Demyelinating Polyradiculoneuropathy (Aidmentioning
confidence: 99%
“…Given that GBS affects more males than females, this could imply that the immune changes seen with aging in males may be a contributing factor to the pathogenesis of GBS via alterations in B cells. In addition, there have been some studies suggesting that γδ T cells and B cells interact (Häcker et al, 1995 ; Rampoldi et al, 2020 ). More specifically, Häcker et al have found that when autologous B cells were used to stimulate γδ T cells in culture, it led to an increase in the percentage of Vδ1 + cells (Häcker et al, 1995 ).…”
Section: Acute Inflammatory Demyelinating Polyradiculoneuropathy (Aidmentioning
confidence: 99%
“…MAIT-клітини становлять практично 10 % пулу Т-клітин периферичної крові людини. Пул MAITклітин у жировій тканині людини значно більший, ніж у периферичній крові [31,55].…”
Section: популяціїunclassified
“…γδTклітини індукують експресію необхідних костимуляторних молекул B-клітин, включаючи CD40L, CD86, CD70, Рисунок 5. Регуляторна роль γδТ-клітин у жировій тканині OX40 та ICOS, а також підвищують активність синтезу IgM В-клітинами [55]. IFN-γ, TNF-α, GM-CSF, IL-4, які продукуються γδТ-клітинами, сприяють диференціюванню моноцитів в антигенпрезентуючі клітини [70].…”
Section: роль γδT-клітин вродженої імунної системи в розвитку метазапunclassified
“…Different γδ subsets play multiple roles in immune defense and are involved in tissue surveillance, tumor immunity, anti-microbial responses and autoimmunity [ 11 , 12 ]. In addition to cytokine secretion and cytotoxic activity, γδ T cells can interact with B cells, e.g., to promote immunoglobulin class switching [ 13 , 14 ], and are able to present antigens in an MHC-restricted fashion to αβ T cells [ 15 ]. Furthermore, CD16-expressing γδ T cells mediate antibody-dependent cellular cytotoxicity (ADCC) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%